Analisa Dampak Aliran Sungai Terhadap Banjir di Kawasan Pemukiman Brang Bara Kabupaten Sumbawa - Israjunna Israjunna; Didin Najimuddin; Ady Purnama; Tri Satriawansyah; Zulkarnaen Zulkarnaen (Indonesian Journal of Applied Science and Technology, 2020)
Flooding is a problem which until now still needs special handling from the government and the community, the maximum average rainfall in Sumbawa sub-district in 2011 was higher than flood conditions while in 2017 the conditions were lower. Hydrological analysis method obtained value of rainfall intensity for a period of 10 years with a duration of five minutes obtained a figure of 219.872 mm and the results of the design flood calculation with a 25-year return period obtained of 865,925 m3 / second. embankment planning for Mitigation efforts in reducing flood problems on the banks of the Brang Bara river can be done re-planning the flood embankment by raising the embankment, making revetment on the cliffs on the left side of the river so that it is not easy to landslides and river normalization. The results of the study prove that the cause of the flooding is not only from large water discharges but also the increase in the number of residents which causes an increase in the volume of waste dumped into the river, the increase in sedimentation obtained causes the river's capacity to decrease.